2007
DOI: 10.1677/joe-06-0114
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone inhibits proliferation of fetal cardiac myocytes in vitro

Abstract: Thyroid hormone (T 3 ) is a key regulator of fetal organ maturation. Premature elevations of thyroid hormone may lead to a 'mature' cardio-phenotype. Thyroid hormone will stimulate maturation of ovine fetal cardiomyocytes in culture by decreasing their proliferative capacity. Group 1 fetal cardiomyocytes (w135 days gestation) were incubated with T 3 (1 . 5, 3, 10, and 100 nM) and bromodeoxyuridine (BrdU; 10 mM) for 24 and 48 h. Group 2 cardiomyocytes were cultured with T 3 alone for later protein analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 43 publications
3
72
0
1
Order By: Relevance
“…They promote a switch from proliferation to hypertrophy and differentiation of the cardiomyocytes both at term and earlier in gestation (Chattergoon et al 2012a,b). In a series of in vivo and in vitro studies in fetal sheep, T 3 has been shown to increase the cardiomyocyte size and the population of terminally differentiated binucleated cells in association with downregulation of cell cycle promoters by 50% or more and upregulation of cell cycle suppressors and various molecular mechanisms of cell growth by up to 500% (Chattergoon et al 2007(Chattergoon et al , 2012a. Conversely, thyroidectomy of the sheep fetus reduces the number of binucleate cardiomyocytes by 27% and the relative weight of the heart by 10-15% near term (Chattergoon et al 2012a, Segar et al 2013.…”
Section: The Heart and Cardiovascular Functionmentioning
confidence: 99%
“…They promote a switch from proliferation to hypertrophy and differentiation of the cardiomyocytes both at term and earlier in gestation (Chattergoon et al 2012a,b). In a series of in vivo and in vitro studies in fetal sheep, T 3 has been shown to increase the cardiomyocyte size and the population of terminally differentiated binucleated cells in association with downregulation of cell cycle promoters by 50% or more and upregulation of cell cycle suppressors and various molecular mechanisms of cell growth by up to 500% (Chattergoon et al 2007(Chattergoon et al , 2012a. Conversely, thyroidectomy of the sheep fetus reduces the number of binucleate cardiomyocytes by 27% and the relative weight of the heart by 10-15% near term (Chattergoon et al 2012a, Segar et al 2013.…”
Section: The Heart and Cardiovascular Functionmentioning
confidence: 99%
“…Both TH-mediated up-and down-regulation of cyclins have been demonstrated in several tissues (Ledda-Columbano et al 2005, Chattergoon et al 2007, Verga Falzacappa et al 2012. TH-mediated regulation of cyclin-CDK complexes leading to cell arrest (Toms et al 1998) or cell differentiation (Ballock et al 2000) has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that physiological concentrations of T 3 are powerful suppressants of serum-stimulated proliferation among isolated cardiomyocytes from mid-and late-gestation (7,8). The inhibitory effect is associated with increases in the cell cycle suppressant protein, p21, and decreased expression of the cell cycle protein, cyclin D1.…”
mentioning
confidence: 97%
“…Among the many regulators, insulin-like growth factor 1 (IGF-1) (44) powerfully stimulates proliferation rates of ovine cardiomyocytes and is the most powerful factor in promoting robust growth in the heart. In opposition to IGF-1, thyroid hormone is a powerful antiproliferation hormone that becomes increasingly effective as gestation proceeds (7). Thus the balanced actions of these two hormones determine the cardiomyocyte endowment at birth.…”
mentioning
confidence: 99%